Numerical evaluation of the effect of swirl configuration and fuel-rich environment on combustion and emission characteristics in a coal-fired boiler. (1st April 2023) - Choi, Minsung; Hwang, Taegam; Park, Yeseul; Li, Xinzhuo; Kim, Junsung; Kim, Kibeom; Sung, Yonmo; Choi, Gyungmin
Abstract: A numerical evaluation using mesh and models verified by comparison with experimental results was performed to investigate the effects of swirl configuration and fuel-rich environment on the flame phenomenon, uniformity of coal particles, and combustion characteristics in a 16-kWth coal-fired boiler. In addition, the suitability of the application of existing technologies to coal-fired power generation to reduce pollutant emissions and enhance the combustion efficiency was evaluated by calculating environmental costs based on the life cycle assessment method. The coal particles of the co-swirling flame were more uniformly dispersed than those of the counter-swirling flame because of the generation of the inner recirculation zone and exhaust tube vortex. Therefore, the burnout zone was evenly formed inside the boiler. Counter-swirling flames exhibit proportional results in terms of the increase or decrease in NOx emissions and unburned coal particles (UCPs) with swirl intensity. However, co-swirling flames have a synergistic effect that can reduce the NOx and UCPs emissions up to 102.4 ppm (@6%O2 ) and 1.23 g/m 3, respectively. Considering the external environmental costs for NOx, SO2, CO2, and UCPs emissions for all fuel-rich environments, the application of air staging technologies can reduce the environmental costs from $0.003 to $0.015 per day. Highlights: Numerical evaluation was performed in a coal-fired boiler using deNOx technologies. Effects of swirl configuration on three major NOx emissions were investigated. Co-swirl flame was effective in reducing NOx emissions and unburned coal particles. Fuel-rich environment was applied to evaluate the combustion characteristics. Air staging was beneficial for the environmental cost and operational goals.